Perceptions of support staffs on English usage at the workplace / Samsiah Bidin and Aishah Musa - Bidin, Samsiah; Musa, Aishah (Universiti Teknologi MARA, Kedah, 2011)
Much has been said that universities in Malaysia have to increase the intake of foreign students. One of the purposes is to rank Malaysian universities among the top World Class Universities. Due to this, there is a growing concern of the use of English language at the public universities especially among the support staff. Hence, this study was conducted to find out the perceptions of the support staff at the Malaysian public universities at the Northern Region regarding English usage by examining the workers’ needs and actual use of language at the workplace, the workers’ wants, and the workers’ lacks in English language. It was found that English is not necessary for the support staff in performing their duties. However, English is more needed for personal usage. It is hope that the findings of this study will provide insights to employers to better manage the workplace literacy particularly when English is concern.